Precision Irrigation Systems for Sustainable Water Management in Maize Cultivation: Impact on Yield and Water Use Efficiency - Kundu, Arnab; Waris, Sadia; Sanam, Shagufta; Aslam, Hira; Khan, Buhram; Bogati, Sindhu Kumari; Rizwan, Muhammad; Muhammad Jamshed,; Majeed, Muhammad Saad; Mohammad Ashfaq, (Indus Journal of Bioscience Research, 2025)
This research aims at evaluating the effectiveness of precision irrigation systems in increasing yield and water productivity in maize production. While it is well understood that the technology offers the ability to apply water selectively and, therefore, be resource-saving, the potential benefits in practice have not been researched adequately. Quantitative data was obtained through survey administration with 50 maize farmers on the use and perception of precision irrigation. Descriptive and inferential analytical tools such as Chi-Square tests, t-tests and regression analysis were used to test the hypothesis that precision irrigation practices has positive effects on crop yields and water use. The results suggest that precision irrigation technologies do not increase crop productivity or water use efficiency in the sample analyzed. The correlation and regression tests showed no meaning co-efficient and there were no correlations for most variables and no impacts were found in variance analysis either, moreover, the R-squared in regression analysis was very low, thus there might be other factors that could be possibly more important for defining the results of maize production The research also finds that despite the potential advantages of precision irrigation systems, their implementation does not improve crop yield or water use in the examined scenario. This underlines the fact that agricultural systems are highly differentiated and that is why it is necessary to take into account the local conditions in order to use such technologies.